Pengaruh Model Pembelajaran Pair Check terhadap Kemampuan Koneksi Matematis Siswa Kelas X MAN 1 Banyumas - Ana Fikri Fitrias; Fitria Zana Kumala (Universitas Veteran Bangun Nusantara, 2023)
This research aims to determine the influence of the pair check learning model on the mathematical connection ability of class X MAN 1 Banyumas students. This study falls under the category of quasi-experimental design research. Four hundred seventy-six students in class X MAN 1 at Banyumas served as the study's population. The sampling method employs a straightforward random sampling technique, in which samples are drawn randomly from the population without regard to their position. The two most notable classes from this research are X-2, which has 38 students and serves as an experimental school, and X-4, which has 38 students and serves as a control school. Instruments in the form of test questions were used to gauge participants' proficiency with mathematical connections. The data analysis technique using the N-Gain test showed a difference in the average N-Gain in the experimental class, which was 0.4727 more than the control class N-Gain value of 0.2354. Accordingly, it can be inferred that class X MAN 1 Banyumas' ability to make mathematical connections is impacted by the application of the pair check learning model.